Übersetzungsstrategien von Grimms Rotkäppchen am Beispiel polnischer Übersetzungen - EBERHARTER-AKSU, MARGIT; HINC, JOLANTA (Glottodidactica, 2019)
The fairy tales of the Brothers Grimm belong to the best-known literary works of Germany, besides the Luther Bible. They are currently published in 160 languages and have been part of the World Documentary Heritage since June 2005. In Poland, they are known in countless translations, adaptations and retellings, some of which have been greatly modified and adapted for teaching purposes and others are literally based on the original texts. The empirical part of the article refers to an experiment in which 19 subjects were presented with a translation task: to transfer selected passages of Little Red Riding Hood into Polish. In the runup to the study, it was hypothesized that the information about the status of the work as part of the World Document Heritage given to study participants should have an effect on the literal translation. The results of the experiment do not confirm the assumed hypothesis, but clearly show that the translation variants above all have to be seen as a continuation of the individual’s experiences with the fairy tale, which strongly influences that individual’s translation.